Optimization of Gamma-Aminobutyric Acid Production by Lactiplantibacillus plantarum FRT7 from Chinese Paocai - Hongying Cai; Xuan Li; Daojie Li; Weiwei Liu; Yunsheng Han; Xin Xu; Peilong Yang; Kun Meng (Foods, 2023)
Gamma-aminobutyric acid (GABA) is a widely available non-protein amino acid whose physiological importance goes beyond its role as an inhibitory neurotransmitter in mammals. The GABA synthesis ability of ten strains of Lactiplantibacillus plantarum was screened. They produced GABA ranging from 48.19 ± 3.44 to 100.75 ± 1.63 mg/L at 24 h-cultivation. Among them, Lp. plantarum FRT7 showed the highest GABA production. Therefore, FRT7 was chosen for GABA yield optimization. A one-factor-at-a-time strategy analysis of the GABA yield of FRT7 was performed, including the culture temperature, incubation time, inoculum volume, initial pH, the initial amount of monosodium glutamate (MSG), and pyridoxal 5’-phosphate (PLP) concentration, based on which the response surface methodology (RSM) was performed. After being cultured in an MRS culture medium supplemented with 3% MSG and 2 mmol/L of PLP at 40 °C with an initial pH of 7.0 for 48 h, the GABA reached a maximum yield of 1158.6 ± 21.22 mg/L. The results showed the experimental value of the GABA yield was in good agreement with the predicted values. Furthermore, the results from the RSM also indicated that the initial MSG addition, PLP concentration, and incubation time were significant variables. These results suggest that Lp. plantarum FRT7 has the potential to be a health-beneficial probiotic with commercial capabilities.